Pengalaman Keluarga Merawat Klien Gangguan Jiwa Pasca Pasung - Hanik Endang Nihayati; Dwi Adinda Mukhalladah; Ilya Krisnana (Universitas Airlangga, 2016)
Introduction: Post restraint is a person who is free from restraint. This study aims to describe about family experience in taking care of client mental disorders post restraint. The biggest problem in the family who has experience taking care of client mental disorders post restraint, among others, always assisting client in their daily activities and ensuring client are already taking the drugs. Method: This study used phenomenology design with six partisipan using indepth interview. The participant of this study was a member family caring for client mental disorders post restraint. This study employs the purposive sampling method. Result: After his release restraint , clients of mental disorders has also increased compared to when the restraint. Despite progress, the family still observe physical development , provide activities to ODGJ , and bring to healthcare. Families experiencing barriers for taking care of client mental disorders post restraint and some are not experiencing barriers. During the care of the clients , the family hopes a change in the client's health status and health change. The family also supports so that clients with mental disorders speedy recovery. Discussion: Family experience in taking care of client mental disorders post restraint are grateful that after restraint off the client state is getting better. The family also regularly check the client to the health worker. In addition, families will no longer restraint clients such mental disorders. Family need an intervention for strengthen coping mechanisms for dealing with various problems in caring for clients with mental disorders after restraint. These activities can be realized through the provision of counseling services and health workers always control the family as well as the client.